THE IMPLEMENTATION OF INDUCTIVE TEACHING AND LEARNING METHODS IN ISLAMIC EDUCATION LEARNING - Rosyad, Ali Miftakhu (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2019)
The article aims to describe the essence of inductive method in Islamic education learning. The learning will run optimally if the teacher utilize the suitable approach and method.Traditional engineering instruction is deductive, beginning with theories and progressing to applications of those theories. Alternative teaching approaches are more inductive. The Islamic education learning should be utilized the inductive method. Topics are introduced by presenting specific observations, case studies or problems, and theories are taught or the students are helped to discover them only after the need to know them has been established. Factually, in modern era the Islamic education learning must be innovated for answering the globalization demand.